The Ontology-Based Methodology Phases To Develop Multi-Agent System (OmMAS) - Arda Yunianta; Aina Musdholifah; Nataniel Dengen Haviluddin; Omar Obarukab Norazah Yusof; Herlina Jayadiyanti; Mohd Shahizan Othman (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Semantic aspect on methodology phase is a significant  issue  to  develop  multi-agent  system in  the  current days.   There are a lot of methodologies to develop multi-agent system, but the current problem is how to choose the best methodology phase to develop current multi-agent system. The development of multi-agent system currently is to be more complex and difficult. Many aspects that contains on multi-agent system, the one of the famous issue now is about semantic aspect on multi-agent system. The old methodology phases are not suitable to develop current multi-agent system. Nowadays, many researchers start to improve and customize the obsolete methodology to adjust with the current needed. There are two research steps contains in this paper, the first step is to review and criticize previous methodologies especially about MOMA (Methodology for Developing Ontology-Based Multi-Agent System) was introduced in 2013. The second step is the main contribution of this paper is to improve previous methodology phases with the new methodology phases named OmMas (The Ontology-Based Methodology phases to Develop Multi-Agent System), and using semantic aspect as the  main focus of this methodology. The result of this research is improved ontology- based methodology phases as a representation of semantic aspect on the ontology development process.